Hormonal treatment of acne vulgaris: an update - Elsaie ML (Dove Medical Press, 2016)
Mohamed L Elsaie Department of Dermatology and Venereology, National Research Centre, Cairo, Egypt Abstract: Acne vulgaris is a common skin condition associated with multiple factors. Although mostly presenting alone, it can likewise present with features of hyperandrogenism and hormonal discrepancies. Of note, hormonal therapies are indicated in severe, resistant-to-treatment cases and in those with monthly flare-ups and when standard therapeutic options are inappropriate. This article serves as an update to hormonal pathogenesis of acne, discusses the basics of endocrinal evaluation for patients with suspected hormonal acne, and provides an overview of the current hormonal treatment options in women. Keywords: acne, hormones, hyperandrogenism